SPICE PATH IN COMPASS ONLINE MEDIA CONSTRUCTION 2017-2021: HISTORICAL PERSPECTIVE - Benny Agusti Putra (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2022)
The spice route is one of the important issues going forward by the Government of Indonesia, to make Indonesia a world maritime axis, this issue is not just a textual discourse, but the issue of the spice route is one of the visions and missions of the Joko Widodo Government in Nawacita to apply it. Historical terminology from various studies from the 7th century to pre-independence, of course, with the scope of this study, it becomes a benchmark for reviewing the issue of the spice route, not historical studies but other studies that can add to the wealth of knowledge about the spice route. Media research in a historical perspective with historical issues in Indonesia has not been widely studied, one of which is the study of the spice route. The researcher tries to see the spice route in the construction of the online media Kompas historical perspective, using the content analysis method, which consists of several stages: 1. Data collection on the spice route news in the online media Kompas from 2017-2021, 2. Source criticism. 3. Interpretation of the spice path in the online media construction of Kompas, by conducting intensive literature and documentation studies, which are descriptive in content analysis, aiming to describe or explain what online news is, it must reach the explanation stage. Indicators from the analysis content are described, such as heuristics, sources, and historical writing contained in the Kompas online media coverage themes.Jalur rempah salah satu isu penting ke depan oleh Pemerintahan Indonesia, untuk menjadikan Indonesia menjadi poros maritim dunia, isu ini tidak sekadar wacana secara tekstual, tetapi isu jalur rempah ini menjadi salah satu visi misi Pemerintahan Joko Widodo didalam Nawacita untuk meaplikasikannya. Terminologi sejarah dari berbagai kajian dari abad ke-7 sampai prakemerdekan, tentu dengan ruang lingkup kajian tersebut menjadi patokan untuk mengkaji lagi tentang isu jalur rempah tersebut, bukan kajian sejarah tetapi kajian-kajian lain bisa menambah kazanah ilmu pengetahuan tentang jalur rempah. Penelitian media dalam perspektif sejarah dengan isu-isu sejarah di Indonesia belum banyak dikaji, salah satunya kajian tentang jalur rempah. Peneliti mencoba melihat jalur rempah dalam konstruksi media online Kompas perspektif sejarah, dengan menggunakan metode conten analisis, yang terdiri beberapa tahapan: 1. Pengumpulan data berita jalur rempah di media online Kompas dari 2017-2021, 2. Kritik Sumber. 3. Interpretasi jalur rempah dalam konstruksi media online Kompas, dengan melakukan studi kepustakaan dan dokumentasi intensif, yang bersifat deskriptif conten analisis, bertujuan mendeskripsikan atau menjelaskan apa adanya berita online harus sampai ketahap eksplanasi. Indikator dari dalam konten analisis diuraikan seperti, heuristik, sumber, dan penulisan sejarah yang terkandung didalam tema-tema pemberitaan media online Kompas.